2018
DOI: 10.18632/oncotarget.25686
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of CDK18 expression in breast cancer to clinicopathological parameters and therapeutic response

Abstract: BackgroundCyclin-Dependent Kinases (CDKs) are established anti-cancer drug targets and a new generation of CDK inhibitors are providing clinical benefits to a sub-set of breast cancer patients. We have recently shown that human CDK18 promotes efficient cellular responses to replication stress. In the current study, we have investigated the clinicopathological and functional significance of CDK18 expression levels in breast cancers.ResultsHigh CDK18 protein expression was associated with a triple negative and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…We found that genes that participate in important events for tumorigenesis could generate alternatively-spliced isoforms. Genes participating in cell cycle progression and genome stability such as CDK18 [25] present potential isoforms in PA. Similarly, THY1 genes which participate in T-cell activation, apoptosis, cell migration, cell adhesion and extravasation [26] also present splicing generated isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…We found that genes that participate in important events for tumorigenesis could generate alternatively-spliced isoforms. Genes participating in cell cycle progression and genome stability such as CDK18 [25] present potential isoforms in PA. Similarly, THY1 genes which participate in T-cell activation, apoptosis, cell migration, cell adhesion and extravasation [26] also present splicing generated isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinases (CDKs) are established anti-cancer drug targets, and a new generation of CDK inhibitors provides clinical benefits to the patients. Breast cancer cells were genetically manipulated using a deactivated CRISPRs/Cas9 (dCRISPR) approach to strengthen the endogenous CDK18 promoter to express highly to exhibit an increased sensitivity [41].…”
Section: Cancermentioning
confidence: 99%
“…Another important example is constituted by CDK18, whose role was recently identified by studies in Collins laboratory [3]. Further studies in the accompanying manuscript not only identified CDK18 as an important regulator of DNA replication stress signalling, but also provided novel insights on its role in breast cancer progression [4].…”
mentioning
confidence: 99%
“…High CDK18 protein expression could predict a better response to chemotherapy. These data suggest that CDK18 mRNA and protein levels are regulated differently within cancer cells with potentially distinct predictions on outcome for patients [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation